Development of Interlocking Masonry Bricks and its' Structural Behaviour: A Review Paper - Al-Fakih, A. (Institute of Physics Publishing, 2018)
Conventional bricks are the most elementary building materials for houses construction. However, the rapid growth in today's construction industry has obliged the civil engineers in searching for a new building technique that may result in even greater economy, more efficient and durable as an alternative for the conventional brick. Moreover, the high demands for having a speedy and less labour and cost building systems is one of the factor that cause the changes of the masonry conventional systems. These changes have led to improved constructability, performance, and cost as well. Several interlocking bricks has been developed and implemented in building constructions and a number of researches had studied the manufacturing of interlocking brick and its structural behaviour as load bearing and non-load bearing element. This technical paper aims to review the development of interlocking brick and its structural behaviour. In conclusion, the concept of interlocking system has been widely used as a replacement of the conventional system where it has been utilized either as load bearing or non-load bearing masonry system. Â© 2018 Published under licence by IOP Publishing Ltd.